Mohammed Abid Jābirī, Reformasi Hukum Islam Dan Pembaruan Pengetahuan - M Nur Kholis Al Amin (Universitas Cokroaminoto Yogyakarta, 2019)
Religious reform and renewal of knowledge are common to the lives of religious and state people. The relationship between the two in the modern era is a matter of concern in the world of politics, so that the study of Islamic politics has developed quite significantly, which includes the study of the relationship between Islam and the State, as well as the impact of that relationship which leads to democracy and its concepts, human rights, and the movement of the ulama (Muslim scholars) towards religious reform. Therefore, one of the Muslim leaders, namely Mohammed Abid Jābirī who is one of the phenomenal figures of revolutionary Islamic thinkers with his theses on various real advances in human life, both in his studies of: the social environment or the development of sacred texts Muslims, which in this case is specifically in the study of the relationship between Religion and the State, Democracy, Khilafah Theory, and Religious Reform through renewal of knowledge. That is what later became the main and interesting discussion to be examined through the relationship approach between Religion and the State through the framework of a fundamental, secular and substantive school of thought. The analysis of MA Jābirī's views on religious reform and knowledge renewal focused on the relationship between Religion and the State in the Modern Age, which was then analyzed by the author using a combination of Al-Mawardi's views in Al-Ahkam Al-Sulthaniyyah, Agus Maftuh Abegebriel and Ahmad Yani Abeviero through his paper Negara Tuhan; The Thematic Encyclopaedia, and the development of democratic issues in the Islamic and Western world as an inseparable relationship when discussing Religion and the State as substantic.